Nanoindentation as a Method for Determining the Mechanical Properties of Cold Spray Coatings - Medard Makrenek (Communications - Scientific letters of the University of Zilina, 2021)
The paper presents the methodology behind the statistical selection of input parameters using the example of spraying two cold-sprayed coatings. The Ti and Cr3C2-25(Ni20Cr)-Gr coatings were tested. Despite the large difference in the structure of these coatings, nanoindentation studies were carried out focusing on the nano hardness H and elastic modulus E. Based on the four input parameters and two output parameters, a 2-level factorial 2(k-p) experimental design was performed. The conducted analysis showed the significant influence of the spray distance on the H and E values in the case of the Ti coating. The input parameters of the spray distance and the type of carrier gas used turned out to be statistically significant in the case of the cermet coating. Taking into account the statistical analysis, the coatings were sprayed with modified values of the input parameters.